Systematic Literature Review: The Impact of Divorce on Children's Mental Health - Wasono, Andy; Mulawarman, Mulawarman; Mulyani, Petra Kristi; Kumalasari, Erny; Mubarak, Muh. Azhar; Arinanta, Firdian Setiya; Salafudin, Moh. Anwar (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The increase in divorce cases has raised concerns about the psychological well-being of affected children, with the risk of anxiety, depression, and behavioral disorders. The purpose of this writing is to find out the impact of divorce on children's mental health. The method used is a systematic literature review using databases from PubMed and ScienceDirect. The search was carried out using the keywords children, divorce, marital dissolution, mental health. Article screening used the PRISMA method and 8 articles were found that were in accordance with the research topic. The results showed that divorce increased the risk of mental problems such as anxiety, depression, behavioral problems, and decreased academic performance. In addition, children from divorced families face a higher risk of mental disorders. High parental conflict exacerbates negative effects, while good social and emotional support can reduce those adverse effects. This study highlights the importance of paying special attention to the mental well-being of children post-divorce to prevent adverse long-term effects. It is hoped that the results of this study can deepen the understanding of the impact of divorce and help develop support strategies for children who have experienced parental divorce, in order to reduce the risk of long-term mental health disorders. Keywords: Children, Divorce, Marital Dissolution, Mental Health